The improving strategies and applications of nanotechnology-based drugs in hepatocellular carcinoma treatment - Ren, Xiangyang; Su, Danyang; Shi, Doudou; Xiang, Xiaohong (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatocellular carcinoma (HCC) is one of the leading causes of tumor-related death worldwide. Conventional treatments for HCC include drugs, radiation, and surgery. Despite the unremitting efforts of researchers, the curative effect of HCC has been greatly improved, but because HCC is often found in the middle and late stages, the curative effect is still not satisfactory, and the 5-year survival rate is still low. Nanomedicine is a potential subject, which has been applied to the treatment of HCC and has achieved promising results. Here, we summarized the factors affecting the efficacy of drugs in HCC treatment and the strategies for improving the efficacy of nanotechnology-based drugs in HCC, reviewed the recent applications’ progress on nanotechnology-based drugs in HCC treatment, and discussed the future perspectives and challenges of nanotechnology-based drugs in HCC treatment.